2018
DOI: 10.1371/journal.pgen.1007532
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies a susceptibility locus for biliary atresia on 2p16.1 within the gene EFEMP1

Abstract: Biliary atresia (BA) is a rare pediatric cholangiopathy characterized by fibrosclerosing obliteration of the extrahepatic bile ducts, leading to cholestasis, fibrosis, cirrhosis, and eventual liver failure. The etiology of BA remains unknown, although environmental, inflammatory, infectious, and genetic risk factors have been proposed. We performed a genome-wide association study (GWAS) in a European-American cohort of 343 isolated BA patients and 1716 controls to identify genetic loci associated with BA. A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 64 publications
1
66
3
Order By: Relevance
“…Several genome‐wide studies of single‐nucleotide polymorphisms or copy number variations and cDNA microarray studies in BA patients have associated few susceptible genes with this disease . For example, adducin 3, ADP ribosylation factor 6, ECM‐related genes, endothelial growth factor containing fibulin extracellular matrix protein 1, glypican 1, x‐prolyl aminopeptidase 1, and genes for several transcription factors are associated with both embryonic and perinatal BA.…”
Section: Discussionmentioning
confidence: 99%
“…Several genome‐wide studies of single‐nucleotide polymorphisms or copy number variations and cDNA microarray studies in BA patients have associated few susceptible genes with this disease . For example, adducin 3, ADP ribosylation factor 6, ECM‐related genes, endothelial growth factor containing fibulin extracellular matrix protein 1, glypican 1, x‐prolyl aminopeptidase 1, and genes for several transcription factors are associated with both embryonic and perinatal BA.…”
Section: Discussionmentioning
confidence: 99%
“…While this condition is relatively rare with an estimated birth prevalence of 0.7–0.9 per 10,000 births (Caton, Druschel, & McNutt, ; Yoon, Bresee, Olney, James, & Khoury, ), biliary atresia is the most common cause of extrahepatic obstructive jaundice in the newborn and the most frequent indication for liver transplantation in children (Sundaram et al, ; Yoon et al, ). Four independent GWAS of biliary atresia among relatively small cohorts of patients (35–499 patients) have identified four novel biliary atresia susceptibility loci (Table ): (a) an intergenic locus on 10q24.2 between ADD3 and XPNPEP1 (Garcia‐Barcelo et al, ); (b) a deletion in 2q37.3 that included AGXT and GPC1 (Cui et al, ); (c) ARF6 (Ningappa et al, ); and (d) EFEMP1 (Chen et al, ).…”
Section: Gwas Of Selected Birth Defectsmentioning
confidence: 99%
“…: (a) an intergenic locus on 10q24.2 between ADD3 and XPNPEP1 (Garcia-Barcelo et al, 2010); (b) a deletion in 2q37.3 that included AGXT and GPC1(Cui et al, 2013); (c) ARF6(Ningappa et al, 2015); and (d) EFEMP1(Chen et al, 2018).…”
mentioning
confidence: 99%
“…Although the etiology of BA is not clear, a genetic component is supported by multiple lines of evidence. These include the presence of familial cases [3][4][5] , case reports of individuals with syndromic BA with likely causal genes identified (including FOXA2 6 , CFC1 7,8 , ZEB2 9 , ZIC3 10 , HNF1B 11 and PKD1L1 12 ), animal models of BA involving the genes Sox17 13 , Foxm1 14 , Invs 15 , Onecut1 16 , and candidate susceptibility genes including ADD3 17 , GPC1 18 , EFEMP1 19 and ARF6 20 identified by genome-wide association studies (GWAS). Genes implicated in syndromic BA function in bile-duct development and the establishment of left-right symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…A GWAS identified SNPs associated with BA upstream of XPNPEP1 and ADD3 in a Chinese cohort of isolated BA patients 17 , and this association has been confirmed in both a Thai 22 and an European-American cohort 23 . In a study of 499 isolated and syndromic BA patients and 1928 controls, our group identified a GWAS signal within 2p16.1 implicating common variants in the gene EFEMP1 19 . Another genome-wide association study of 63 BA patients and 1907 controls identified two SNPs downstream of the gene ARF6 associated with isolated BA 20 , although we could not replicate this finding in our study.…”
Section: Introductionmentioning
confidence: 99%